Occurrence of Bunch Rot Disease Caused by Aspergillus tubingensis on Shine Muscat Grape - Young Soo Kim; Hyeok Tae Kwon; Seung-Beom Hong; Yongho Jeon (Research in Plant Disease, 2019)
During the year 2018, the symptoms of bunch rot on Shine Muscat (Vitis vinifera L.) were observed in Kimcheon-si, Gyeongbuk province in Korea. The disease appears on the Shine Muscat as a black rot due to prolific fungal sporulation after it has invaded into the Shine Muscat which look completely empty and dryness. Colonies of these fungi are present on the Shine Muscat skin from fruit setting and increase in amount from early season to harvest, while become peak at ripening stage. To isolate the causal agent, small fragments (2 to 3 mm) of decayed tissue from the lesion margin were placed onto potato dextrose agar (PDA) plates. Fungal colonies on PDA produced dense white aerial mycelium and then covered with dark black conidial heads. These heads were large and radiate, and vesicles were globose (2.12–32.0×2.0–3.1 μm). Based on morphological and cultural characteristics, this fungus was identified as Aspergillus tubingensis. To confirm its identity, the internal transcribed spacer, β-tubulin, and RNA polymerase II was sequenced for molecular identification. BLAST search indicated 99% identity with A. tubingensis. The pathogenicity test on healthy grape of Shine Muscat produced bunch rot, as the original symptoms. To select effective fungicides for the control of brunch rot, an in vitro antifungal activity of seven fungicides were evaluated against the growth of A. tubingensis. Five fungicides (dipenoconazole, tebuconazole, metconazole, iminoctadine, and captan) exhibited significantly strong suppression of the mycelial growth of A. tubingensis.